Hyperreactio luteinalis with preeclampsia - Atis, Alev (Medknow Publications, 2010)
Hyperreactio luteinalis (HL) is a condition associated with bilateral and, in rare cases, unilateral ovarian enlargement due to theca lutein cysts. HL is a benign condition, usually found incidentally at cesarean section, which can appear anaplastic and lead to unnecessary ovarian resection. A 24-year-old woman with 35 weeks of gestation attended with bilaterally enlarged ovaries. She had preeclampsia and preterm contractions. Due to breech presentation of baby and nulliparity and possible severe preeclampsia, she delivered by cesarean section. The ovaries had an anaplastic appearance and a biopsy was taken during cesarean section. Pathology revealed multiple benign theca lutein cysts. There are 51 reported cases of HL associated with a normal pregnancy in the literature. It is estimated that approximately 60% of the cases of HL is not associated with trophoblastic disease and occurs with normal singleton pregnancy. Only three of them were found to be associated with preeclampsia and this is the fourth case. HL may help explain the underlying cause of preeclampsia in these cases. There are multiple benign ovarian lesions in HL, which can mimic ovarian neoplasms. Accordingly, it is important to exclude these from the differential diagnosis via a wedge biopsy and frozen section to avoid unnecessary surgical excision.